Joint Ventures in the South African Construction Industry: Factors Militating against Success - Modisaotsile Patrick Seiso; Babatunde Fatai Ogunbayo; Clinton Ohis Aigbavboa (Buildings, 2023)
Joint construction ventures are a global business partnership approach to accomplishing jointly executed construction objectives. The success of joint ventures is not achieved without militating factors and complexity affecting the process. This study assessed the militating factors against joint venture success in the construction industry in South Africa. A quantitative research approach was adopted, using a purposive sampling technique to select participants for this study. In total, 190 copies of the questionnaire were sent out to construction stakeholders in Gauteng province, South Africa, and 185 copies of the questionnaire were retrieved. Data analysis was conducted in three stages: data reliability and validity, descriptive statistics, and exploratory factor analysis. The exploratory factor analysis (EFA) returned seven factors that provided a relevant understanding of the militating factors against joint venture success: differences in partners’ work values, ineffective regulatory frameworks, undefined goals, clashes between partners’ cultural values, economic viability, operational constraints, and conflicts of interest. This study recommends that joint venture formulation requires due diligence from partners to understand policy, organisational culture, sharing ratios, and economic viability to avoid unnecessary conflicts of interest and operational constraints.